A changing of the garden: evaluating the performance and ecosystem functionality of alternative oyster garden structures in residential waterways - Sakr, Adrian; Mazor, Logan D.; Milbrandt, Eric C.; Morton, Joseph P.; Altieri, Andrew H. (Frontiers in Ecology and Evolution, 2025)
Oyster gardening, in which hanging oyster recruitment substrates are suspended from docks, has become an increasingly common and accessible technique for coastal communities to support local oyster populations for biodiversity enhancement, habitat restoration, and ecological functions including water filtration. However, little research has been done to evaluate materials and methods for oyster garden structures regarding cost, ease of assembly, durability, and ecosystem benefits, making it difficult to scale up efforts and maximize project success and sustainability. We conducted a field experiment in a residential canal system on Sanibel Island, Florida where we deployed a variety of oyster garden structure types to evaluate their performance in oyster recruitment, durability, water filtration rate, and biodiversity. Additionally, the occurrence of Hurricane Ian during the deployment provided an opportunity to evaluate how these structures resisted severe storm events. We tested a total of five structures: (1) a conventional design made of drilled oyster shell on steel wire (shell structures); and four alternatives, (2) GROW concrete discs (disc structures); (3) jute fiber coated with calcium sulfoaluminate cement (jute structures); (4) BESE biodegradable plastic matrix panels (BESE matrix panel structures); and (5) BESE biodegradable plastic mesh bags filled with oyster cultch (bag structures). All structures survived Hurricane Ian; however, both BESE structure types ultimately disintegrated without recruiting oysters. Disc, jute, and shell wire structures demonstrated similarly high levels of durability, oyster recruitment and growth, and biofiltration. Thus, we conclude that structure type selection may be based on material and labor availability and whether cost and biodegradability are prioritized. We show that oyster gardening can provide ecosystem services, including biofiltration, in residential canal sites that have lost “natural” shoreline morphology. Investments in oyster gardening are low risk in the face of natural hazards, supporting the use of the practice in storm-prone areas. However, residential canals are prone to adverse water quality, including low dissolved oxygen, which we show may undermine oyster survival and growth in certain cases; location and season thus need to be considered for garden deployment. Our results reveal material options for providing sustainability, durability, oyster recruitment, and biodiversity for oyster gardening projects while minimizing adverse environmental impacts.